Absence of beneficial effects on rabbit sperm cell cryopreservation by several antioxidant agents. Issue 1 (February 2015) - Maya-Soriano, M.J.; Taberner, E.; Sabés-Alsina, M.; Piles, M.; Lopez-Bejar, M.
Summary The generation of reactive oxygen species associated with cryopreservation could be responsible for mammalian sperm damage and the limitable value of stored semen in artificial insemination. The aim of this study was to assess several antioxidant agents supplemented in a commercial freezing extender (Gent B®) in order to improve post-thaw rabbit sperm quality. Ejaculates of 26 New Zealand White rabbit bucks were collected, evaluated and frozen using a conventional protocol. Antioxidant agents were tested at different concentrations: bovine serum albumin (BSA; 5, 30 or 60 mg/ml), retinol (RO; 50, 100 or 200 μM) and retinyl (RI; 0.282 or 2.82 μg/ml). Per cent viability, morphological abnormalities and intact acrosomes were determined using eosin–nigrosin staining. Motility and progressivity were analyzed by computer-assisted sperm analysis (CASA). In general, all sperm quality parameters were negatively affected by the cryopreservation process, the largest effect seen was for total motility. The addition of antioxidant agents did not improve thaw sperm quality. Furthermore, for RI groups a significant decrease in sperm quality parameters was recorded. In conclusion, rabbit sperm quality is negatively affected by the cryopreservation process. To our knowledge this report is the first using these antioxidants to supplement rabbit freezing extender. BSA and RO at concentrations used in the study did not improve sperm quality parameters after thawing, whereas RI supplementation appeared to be toxic. More studies are required to find the appropriate antioxidants necessary and their most effective concentrations to improve rabbit post-thaw sperm quality.